Model Spasial Regionisasi dan Rujukan Fasilitas Kesehatan - Krama, Agel Vidian; Qamilah, Nurul (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Location Hospital and Health Center in Bandar Lampung and the District Pesawaran not currently mapped by conventional or digital. And there is no data base that provides information about the location and distribution of hospitals and health centers in Bandar Lampung City, and the uneven number of health facilities to ensure the availability of health services for all citizens, by optimizing existing health care facilities. Contributions utilization of spatial studies in the health field is used for mapping and modeling of health in order to facilitate access, provision of efficiency and planning of health services in order to take policy related to determining the location of health facilities. The research method uses spatial model approach with descriptive research type and analysis through the use of Huff Model. The results of the regionization shows the coverage area of hospital services serving 33 points in the District Pesawaran and 24 point Population in Bandar Lampung with the spread of regionization is divided into 3 regions. Keywords: Health Service, Regionalization